Infectious Disease as a Modifiable Risk Factor for Dementia: A Narrative Review - Thomas J. Farrer; Jonathan D. Moore; Morgan Chase; Shawn D. Gale; Dawson W. Hedges (Pathogens)
This narrative review examines infectious diseases as modifiable risk factors for dementia, particularly in the context of an aging global population. As the prevalence of Alzheimer’s disease and related dementias is expected to rise, prevention has become increasingly important due to the limited efficacy of current treatments. Emerging evidence links specific infectious diseases to increased dementia risk, possibly through mechanisms like neuroinflammation and disruption to normal cell function. Here, we review findings on how viral and bacterial infections contribute to dementia and explore potentially preventive measures, including vaccinations and antiviral treatments. Studies indicate that vaccinations against influenza, herpes zoster, and hepatitis, as well as antiviral treatments targeting human herpesvirus, could reduce the incidence of dementia. Additionally, non-pharmaceutical interventions during pandemics and in long-term care settings are highlighted as effective strategies for reducing the spread of infectious diseases, potentially lowering dementia risk. Putative mechanisms underlying the protective effects of these interventions suggest that reducing systemic inflammation may be important to their efficacy. While the currently available evidence suggests at best an association between some infectious diseases and dementia, this narrative review emphasizes the need to incorporate infectious disease prevention into broader public health strategies to potentially mitigate the growing burden of dementia. Further research is required to explore these preventive measures across diverse populations and to deepen our understanding of the biological mechanisms involved.